KONTRIBUSI SYALTUT DALAM REFORMASI HUKUM ISLAM - Badwi, Ahmad (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2013)
Thoughts Syaltut a role model for most of the Egyptian Muslims and even other Muslims in Islamic countries through their readings of the books he wrote. Syaltut considered a mujtahid are popular, because of his ideas and his thoughts can be accepted by the majority of Muslims, especially once the scientists of the Islamic countries. His books are reviewed and scrutinized by people outside of Egypt. Syaltut their thoughts and discuss their learning and many of them are making figure Syaltut and pernikiran - thinking as a comparative study and a lot of students who earn a masters degree , even a doctorate to discuss and examine the books and thoughts . Not only the Egyptians who provide feedback and appreciation for their thoughts and ideas , and even the international community recognizes its scientific capabilities , such as when he describes the legal position at the Congress of International Law in The Hague (the Netherlands), his views accepted and welcomed the experts and academics